A Greater Rate of Return to High-Impact Sports Favoring Unicompartmental Knee Arthroplasty Compared with Total Knee Arthroplasty: A Systematic Review with Meta-Analysis - Vossen, Roderick J.M.; ten Noever de Brauw, Gaby V.; van der List, Jelle P; Kerkhoffs, Gino M.M.J.; Pearle, Andrew D.; Zuiderbaan, Hendrik A. (The Journal of Knee Surgery, 2025)
Several studies have demonstrated the importance of patient expectation management following surgery, as this is a crucial factor influencing postoperative outcomes. Informing patients on the likelihood on return to sport (RTS) following a knee arthroplasty is therefore important. This systematic review aimed to compare RTS rates and RTS rates per sport-impact level for primary total knee arthroplasty (TKA), unicompartmental knee arthroplasty (UKA), or patellofemoral knee arthroplasty (PFA). A literature search was conducted in PubMed, Embase, and Cochrane up to June 1, 2024. Studies reporting on RTS rate following TKA, medial UKA, or PFA were included. RTS rates per sport impact level, Tegner–Lysholm, and University of California and Los Angeles (UCLA) activity scores were extracted. Outcomes were compared with meta-analysis using random-effect models. Thirty-eight studies were included for qualitative assessment, of which eight for meta-analysis, comprising 7,634 patients. Meta-analysis demonstrated a significantly greater likelihood for UKA patients (80.7% [18.4–100%]) to RTS than TKA patients (69.0% [4.1–100%]; odds ratio: 1.87 [1.23–2.85], p = 0.004). In high-impact sports, UKA patients (65.4% [18.4–100%]) were able to RTS at a higher rate than TKA patients (TKA 4.4% [4.1–12.5%]). RTS to low- and moderate-impact sports were similar. Postoperative UCLA activity score was superior for UKA patients and postoperative Tegner scores between UKA and TKA were similar. PFA patients returned to sports at a low rate (low-impact 42.4% [41.2–43.5%]; moderate-impact 35.0% [34.8–41.2%]; high-impact 20.5% [17.4–35.3%]). UKA Patients had a significantly higher overall RTS rate than TKA patients. Over 50% of UKA patients were able to return to high-impact sports, whereas only 5% of TKA patients achieved this outcome. The likelihood of RTS appeared lowest among patients who underwent PFA. A more liberal counseling regarding return to high-impact sports following UKA may be justified.
Keywords: knee; replacement; total knee arthroplasty; unicompartmental knee arthroplasty; patellofemoral knee arthroplasty; return to sport; activity